2023
DOI: 10.1186/s12984-023-01150-7
|View full text |Cite
|
Sign up to set email alerts
|

Bimanual movements in children with cerebral palsy: a systematic review of instrumented assessments

Abstract: Background Assessment of bimanual movements, which are frequently impaired in children with cerebral palsy, is highly challenging in clinical practice. Instrumented measures have been developed to evaluate and help to understand impaired upper limb movement during bimanual tasks in these children. The aim of this review was to report instrumented measurement tools (3D motion analysis, sensors, etc.) used for bimanual task movement analysis, and the metrological properties of the measures in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…In the included studies, 84.5% of patients with CP had unilateral impairment, which does not reflect reality as approximately 60% of patients with CP have bilateral impairment [ 121 ]. However, this finding is consistent with previous research [ 21 ] and can again be explained by the large number of quadriplegic patients with severe cognitive impairment [ 122 ]. Yet, patients with bilateral CP are also insufficiently studied using existing clinical tools.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the included studies, 84.5% of patients with CP had unilateral impairment, which does not reflect reality as approximately 60% of patients with CP have bilateral impairment [ 121 ]. However, this finding is consistent with previous research [ 21 ] and can again be explained by the large number of quadriplegic patients with severe cognitive impairment [ 122 ]. Yet, patients with bilateral CP are also insufficiently studied using existing clinical tools.…”
Section: Discussionsupporting
confidence: 93%
“…Most of the reviewed articles used optoelectronic motion capture systems (N = 57/76), which correlates with previous findings [ 15 , 21 , 100 ]. Two articles used the Kinect marker-less motion capture system, 1 article used inertial sensors, 3 used digitizing tablet/instrumented pens, and 4 articles used a joystick/robotic arm (Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In a recent systematic review of quantitative assessments of bimanual movements in children with CP, the authors reported that 3D protocols were heterogenous (1-5 tasks), and the drawer-opening task was the most studied but was not sufficiently representative of bimanual function [13]. The analyses have focused mostly on spatiotemporal variables, some of which were specifically developed to measure bimanual function (e.g., task completion time, goal synchronization).…”
Section: Introductionmentioning
confidence: 99%